Effects of Hypotonic and Isotonic Enteral Electrolyte Solutions Administered in Continuous Flow in Weaned Foals - Monteiro, Lorena Chaves; Viana, Rinaldo Batista; Avanza, Marcel Ferreira Bastos; Ermita, Pedro Ancelmo Nunes; Costa, Caio Monteiro; Alves, Samuel Rodrigues; Santos, Paulo Vinícius de Morais; Silva, Micheline Ozana da; Balbino, Daniel Atila de Barros; Mattos, Felipe Sperandio de; Teixeira, Raffaella Bertoni Cavalcanti; Ribeiro Filho, José Dantas (Frontiers in Veterinary Science, 2020)
The effects of fluid therapy with maintenance enteral electrolytic solutions administered by nasogastric route in continuous flow have not previously been studied in weaned foals. This study had a primary goal compare the effects of two maintenance enteral electrolytic solutions administered by nasogastric route in continuous flow on the hydro electrolytic balance in weaned foals. This paper was a controlled trial in a cross-over design (6x2) performed in six foals with a mean age of 7.3 ± 1.4 months; each animal received two treatments, IsoES and HypoES, with an interval of seven days between treatments. After 12 hours of fasting, the animals were treated with enteral electrolyte solutions administered via nasogastric route in continuous flow in a volume of 15 mL/kg/h for 12 hours. The evaluations were performed at T-12h (the beginning of the fasting), T0h (end of fasting and beginning of fluid therapy), T4h (4 hours of fluid therapy), T8h (8 hours of fluid therapy), T12h (end of fluid therapy), and T24h (12 hours after the end of fluid therapy). Twelve hours of fasting resulted in a reduction (P <0.05) in body weight, abdominal circumference, whereas serum sodium, SID and enophthalmos increased. Twelve hours of fluid therapy normalized these parameters and promoted increased urinary volume and decreased urinary density without causing electrolyte imbalances. Both enteral electrolytic solutions were effective in reestablishing clinical and laboratorial variables without causing electrolyte imbalances.